On the Accumulated Loopback Self-Interference of Two-Way Full-Duplex AF Relaying Systems - Chang, Min-Kuan; Chien, Feng-Tsun; Kuo, Chih-Hung; Chen, Yen-Chang (My University, 2019)
Two-way full-duplex (TWFD) transmissions in cooperative amplify-and-forward (AF) relaying systems provide a promising way of communications with the improved spectral efficiency by concurrently transmitting/receiving data in the same frequency band and by the two-way transmission protocol. However, the loopback self-interference, caused by the imperfect channel estimation in the loopback link, at the AF relay accumulates and is forwarded to the end users recurrently, which substantially degrades the end users' error performance if this accumulated loopback self-interference (ALSI) does not converge. It is therefore of critical importance to analyze the convergence behavior of the ALSI in the TWFD systems with AF relaying. In this paper, we establish sufficient conditions on the relay power to ensure the convergence of the ALSI, with which the average limiting signal-to-interference-plus-noise ratio at the infinite time horizon is derived. In addition, we specify the relay power at which the signal-to-noise ratio reaches the maximal value under different scenarios and obtain an upper bound to the symbol error rate. Finally, extensive computer simulations results are provided to corroborate the analytic derivations.
Keywords: Full-duplex antenna; two-way relaying; amplify-and-forward protocol; accumulation of loopback self-interference (ALSI); stochastic geometric series